2018
DOI: 10.3390/ijerph15040752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traffic Noise and Relaxations Sounds on Pedestrian Walking Speed

Abstract: Exposure to noise in everyday urban life is considered to be an environmental stressor. A specific outcome of reactions to environmental stress is a fast pace of life that also includes a faster pedestrian walking speed. The present study examined the effect of listening to annoying acoustical stimuli (traffic noise) compared with relaxation sounds (forest birdsong) on walking speed in a real outdoor urban environment. The participants (N = 83) walked along an urban route of 1.8 km. They listened to either tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
2
16
3
1
Order By: Relevance
“…The current study continues the previous investigation (Franěk et al, 2018) by using an identical methodology but in different locations and in two diverse seasons. While the previous experiment was conducted in a relatively calm area with a greater amount of greenery, in the current study, the participants were asked to walk along a route that contained areas near both a busy road and a calm alley to test, whether the observed associations between sounds and walking behavior would also occur in a different environment.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…The current study continues the previous investigation (Franěk et al, 2018) by using an identical methodology but in different locations and in two diverse seasons. While the previous experiment was conducted in a relatively calm area with a greater amount of greenery, in the current study, the participants were asked to walk along a route that contained areas near both a busy road and a calm alley to test, whether the observed associations between sounds and walking behavior would also occur in a different environment.…”
Section: Introductionsupporting
confidence: 54%
“…The participants tended to walk statistically significantly faster in areas without greenery and with more traffic and higher perceived noise than in sections with greenery and less traffic and perceived noise. Our previous study (Franěk et al, 2018) found that listening to a soundtrack with traffic noise while walking on an urban route increased the average walking speed. Conversely, listening to a soundtrack with natural sounds (birdsongs) decreased the walking speed in contrast to the control condition, but this difference was not significant.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Noise has also been shown to increase walking speeds in individuals which may influence human perception and enjoyment of locations (Franěk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%